1992
DOI: 10.1037/0278-7393.18.1.89
|View full text |Cite
|
Sign up to set email alerts
|

Effects of automatic associative activation on explicit and implicit memory tests.

Abstract: Ss made either a graphemic or a semantic decision concerning word pairs during a study phase. Pair relatedness effects were observed in behavioral measures for the semantic task only, but a physiological measure (event-related potential) showed relatedness effects for both study tasks. Relatedness at study helped subsequent memory for tests involving word generation (fragment completion and cued recall). These effects were independent of those of the level of processing on memory. The results support Graf and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
40
1
1

Year Published

1994
1994
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 58 publications
3
40
1
1
Order By: Relevance
“…However, there is disagreement concerning the temporal nature of N400 effects: Some experimental results indicated that the amplitude is modulated by lexical processes (e.g., Besson, Fischler, Boaz, & Raney, 1992;Deacon, Hewitt, Yang, & Nagata, 2000); other studies argued that the N400 is sensitive to post-lexical integration (e.g., Brown & Hagoort, 1993;Holcomb, 1993).…”
Section: Frequency and Predictability In Erpsmentioning
confidence: 99%
“…However, there is disagreement concerning the temporal nature of N400 effects: Some experimental results indicated that the amplitude is modulated by lexical processes (e.g., Besson, Fischler, Boaz, & Raney, 1992;Deacon, Hewitt, Yang, & Nagata, 2000); other studies argued that the N400 is sensitive to post-lexical integration (e.g., Brown & Hagoort, 1993;Holcomb, 1993).…”
Section: Frequency and Predictability In Erpsmentioning
confidence: 99%
“…The absence of N400 effects under masking conditions of the prime, therefore demonstrates that automatic spreading of activation is not reflected in the N400. Besson, Fischler, Boaz, and Raney (1992) and Kutas and Hillyard (1989) have presented data on the basis of which they claim that automatic spreading of activation does emerge in the N400. However, their results can also be explained by other priming mechanisms and do not necessitate an explanation in terms of automatic processes (see Chwilla, Brown, & Hagoort, 1995, for an extended discussion of this issue).…”
Section: The Processing Nature Of the N400mentioning
confidence: 99%
“…The results of these ERP studies were not conclusive. Some studies demonstrated N400 priming effects with shallow processing tasks (Besson, Fischler, Boaz, & Raney, 1992;Kutas & Hillyard, 1989). Other studies, however, did not observe N400 priming effects under shallow processing conditions (Bentin, Kutas, & Hillyard, 1993;Deacon, Breton, Ritter, & Vaughan, 1991).…”
mentioning
confidence: 97%
“…The delay between the presentation of the words and the moment subjects were asked to respond might have given subjects ample oppor tunity to in fact perform some kind of semantic matching, in which case the observed N400 priming effect does not necessar ily stem from ASA. A similar argument holds for the study of Besson et al (1992), in which subjects had to indicate whether the first and the last letter of two words that were presented with an SOA of 300 ms were the same or different. In this task, a small (<1 ¿*V) but reliable N400 priming effect was observed.…”
mentioning
confidence: 99%